Improving The Students’ Speaking Skills and The Learning Process of English Speaking Through Information Gap at The Grade XI-IS 2 of the Public Senior High School 7 Malang - misianto, misianto (D3 English Program Universitas Merdeka Malang, 2017)
This Classroom Action Research (CAR) mainly aimed at describing how information gap can improve the students’ speaking skills. The data collection was done by using 3 secondary instruments, namely a pre-test, an observation sheet used by the collaborator, and a student questionnaire. Based on the collected data, the information gap proved effective in improving both the students’ speaking skills and the learning process of English speaking. The detailed results were as follows: Cycle 1: there were 11 of 14 pairs appropriately using Yes/No-questions (78.6 %) and 2 pairs appropriately using WH-questions (14.3 %). As for the answers, 14 pairs were appropriately giving answers (100 %); 12 pairs with appropriate pronunciation (85.7 %) and 2 pairs with appropriate fluency (14.3 %). To be pertinent to the learning process, all of the 14 pairs showed a state of being enjoyable in speaking English (100 %), 12 pairs showing a state of being enthusiastic (85.7 %), all of the 14 pairs showing their seriousness in speaking English (100 %), and 12 pairs managing to accomplish the tasks of speaking English in the given time. In the Cycle 2: all of the 12 pairs appropriately used Yes/No-questions (100 %) and 11 pairs appropriately using WH-questions (91.7 %). As for the answers, all of the pairs were appropriately giving answers (100 %), 10 pairs with appropriate pronunciation (83.3 %), and 11 pairs with appropriate fluency (91.7 %).